Entre o genuíno e o mercadológico : percepções de gays sobre estratégias de marketing em relação a causa LGBTQI+ - Tressoldi, Cassiano (2021)
The LGBTQI+ movement has been the focus of some brands that seek to attract consumers by supporting diversity, often represented in media actions. However, when controversial, this movement causes LGBTQI+ consumers to question it, and strongly criticize these attitudes. Thus, understanding the LGBTQI+ community, movement and history of struggle is a necessary task for those who wish, in some way, to support them. Therefore, I carried out an analysis of gay individuals’ narratives through this work based on the theoretical assumptions of Queer theory, seeking to analyze how heteronormativity affects these individuals’ lives in order to understand how they perceive these attempts at support. Then, anchored in the proposed discussions, I identified which aspects these individuals consider relevant to the brands that wish to embrace LGBTQI+. The results demonstrate objectively how heteronormativity acts on these individuals’ social relationships and, consequently, on the relationships with brands. Still, they indicate that to support the LGBTQI+ community, brands need to consider the history of struggle of the LGBTQI+ community and focus on three main fronts: media diversity; organizational diversity; and the organization's internal culture. This work contributes strongly in making these individuals heard, and for the readers to be able to absorb the history of struggle and the demands of this group. In addition to "doing it right," this research provides important directions for those brands that genuinely want to be catalysts for a positive social change for the LGBTQI+ community.